From Oﬀshore to relocation advantages for logistic improvement in port and for logistic companies - Boyano-Fram, Teóflo Omar (EFIM Ediciones, 2020)
With the great advances of the international management for the mobility of the foreign trade, not only the Ports must be working in the 4 and 5 Generation, also the way to give the service is for that reason that in this article one looks for to make a bet to the oﬀshore that facilitates logistic maneuvers but with the intention of improving the processes of the nations for the beneft and good use of its companies that can lower costs, improve the service and simplify still more the mobility, that is to say to perfect its logistic. It was found that the relocation of companies becomes a competitive logistic position and by using oﬀshore platforms they improve mobility in time, a very important aspect for companies, users and operators or social actors of the logistic maneuver.